Mussel inspired preparation of highly dispersible and biocompatible carbon nanotubes1. Issue 32 (10th April 2015) - Wan, Qing; Tian, Jianwen; Liu, Meiying; Zeng, Guangjian; Li, Zhen; Wang, Ke; Zhang, Qingsong; Deng, Fengjie; Zhang, Xiaoyong; Wei, Yen
<x xml:space="preserve">Abstract</x> A novel method for preparation of water dispersible and biocompatible carbon nanotubes via mussel inspired PEGylation has been developed for the first time.